Intestinal schistosomiasis in remote areas of Southwest Ethiopia, a target region for large-scale mass drug administration - Yared Nigusu; Teshome Bekana; Eshetu Chilo; Sisay Teferi; Dereje Oljira Donacho; Dereje Gemeda; Tefera Darge; Abeza Mitiku; Abdi Geda Gedefa; Tadesse Sime; Wubishet Gezimu; Oda Gizaw; et al. (Scientific Reports)
Abstract As 2030 approaches, the World Health Organization’s due date for ending intestinal schistosomiasis as a public health problem in all endemic areas, understanding the current trends in the burden of schistosomiasis among schoolchildren in endemic areas is critical for monitoring the progress, identifying areas for improvement, and developing strategies to plan for instant response to mitigate the burden of schistosomiasis. From February to April of 2023, 328 students from three primary schools in Southwest Ethiopia participated in an institution-based cross-sectional study in the detection of Schistosoma mansoni. Intestinal schistosomiasis was identified among 242 school children, with a rate of infection of 73.8% (95% CI: (64.8–83.4%)). The rate of infection was higher among study participants aged between 10 and 13 years [AOR = 1.93, 95% CI: (1.1, 3.44). About 75% of the male participants were infected with Schistosoma mansoni [AOR = 0.83, 95% CI (0.49, 1.41). Nearly half (48.1%) of the S. mansoni infections among study participants were identified as heavy infections. More than half of the male study participants (50.3%) infected with Schistosoma mansoni had heavy infection intensity. Of the total female schoolchildren infected with Schistosoma mansoni, about 44.4% had a heavy infection. The prevalence and intensity of infection of Schistosoma mansoni in the study area are significantly noticeable, raising doubts on the effectiveness of the interventional programs or pin-points possible re-infection. Strategies to end the disease as a public health threat, mainly in remote and endemic areas, should consider novel integrated strategies targeting the life cycle of schistosomes besides the large-scale mass drug administration.